Processing large amounts of data in Python for the purposes of applied socio-economic research: advantages and current issues - E. S. Konishchev (Вестник университета)
The article is  devoted to  the study of   the features of   processing large amounts of   data using the Python programming language. Unlike tabular processors or   finished software products, programming languages offer the user a   flexible toolkit for the implementation of   tasks. At   the same time, this creates certain risks associated with the effectiveness of  using appropriate tools and optimising the operation of   the programme. The purpose of   the article is   to study the features of   processing large amounts of   data in   Python on  the  examples of   immediate research tasks. The relevance of   the topic and purpose of  the article is   due to   the existing scientific gap related to a  comprehensive consideration of   the technical aspects of   the use of  programming languages and associated tools for socio-economic research. Thus, many authors who use programming languages in   their works rarely provide information regarding the advantages of   certain algorithms or  approaches. Within the framework of  the article, the author examines the procedures and algorithm of   processing a   large array of   data on   the example of   specific research tasks. The conclusions are drawn about the features and advantages of   Python when working with large amounts of   data as   well as  about the prospects for the development of   the relevant scientific topics.